2013
DOI: 10.1253/circj.cj-12-0982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Predictability of Future Cardiovascular Events Between Chronic Kidney Disease (CKD) Stage Based on CKD Epidemiology Collaboration Equation and That Based on Modification of Diet in Renal Disease Equation in the Japanese General Population

Abstract: Background: Whether estimated glomerular filtration rate (eGFR) calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) Study equation (eGFRCKDEPI) improves risk prediction compared to that calculated using the Modification of Diet in Renal Disease (MDRD) study equation (eGFRMDRD) has not been examined in a prospective study in Japanese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…16 However, the equation is not so accurate for Asian populations, with greater bias at eGFR <60 ml · min −1 · 1.73 m −2 . 17, 18 Accordingly, in this study, eGFR was evaluated by the Japanese version of the equation (J-MDRD): eGFR =194× (serum creatinine) −1.094 × age −0.287 ×0.739 (if female). 19 Additionally, eGFR was also evaluated by the Cockcroft-Gault (CG) equation, 20 which is associated with body weight, because serum creatinine is affected by skeletal muscle mass, which may change after exercise training.…”
mentioning
confidence: 99%
“…16 However, the equation is not so accurate for Asian populations, with greater bias at eGFR <60 ml · min −1 · 1.73 m −2 . 17, 18 Accordingly, in this study, eGFR was evaluated by the Japanese version of the equation (J-MDRD): eGFR =194× (serum creatinine) −1.094 × age −0.287 ×0.739 (if female). 19 Additionally, eGFR was also evaluated by the Cockcroft-Gault (CG) equation, 20 which is associated with body weight, because serum creatinine is affected by skeletal muscle mass, which may change after exercise training.…”
mentioning
confidence: 99%
“…Past studies also found that a moderate to severe decline of GFR is related to high risks of CVD incidence and death [28][29][30]. Recent studies have indicated a U-shaped relationship between estimated GFR (eGFR) and the risk of all-cause death [8,[31][32][33][34]. According to Tonelli et al, the results for normal and higher eGFR levels with or without albuminuria are similar to those for reduced eGFR levels without albuminuria, with both causing high risks of death [31,35], findings which correspond to the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ohsawa et al [18] showed that all-cause mortality and cardiovascular morbidity rates were higher in subjects with normal eGFR (≥90 mL/min/1.73 m 2 ) compared to subjects with mildly decreased eGFR (60-89 mL/min/1.73 m 2 ). Although a linear relationship between cardiovascular events and decreased GFR is usually found, a U-shaped relationship between mortality and stage of chronic kidney disease has been demonstrated in recent reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was determined that this equation overcame the limitation of the MDRD equation (i.e., the underestimation of GFR at given range). [17][18][19][20] Stevens LA et al [20] showed that bias was substantially decreased with the CKD-EPI equation, compared to measured GFR, particularly among people with eGFR greater than 60 ml/min/1.73 m 2 . The study also found that bias was increased using the MDRD equation, when eGFR was greater than 90 ml/min/1.73 m 2 .…”
Section: Is There a Relationship Between Slow Coronary Flow And Normamentioning
confidence: 99%
See 1 more Smart Citation